Evaluation of phytomedicinal potential of perillyl alcohol in an in vitro Parkinson's Disease model. Issue 5 (6th September 2018) - Anis, Ehraz; Zafeer, Mohd Faraz; Firdaus, Fakiha; Islam, Shireen Naaz; Fatima, Mahino; Mobarak Hossain, M
Abstract: Preclinical Research & Development Parkinson's disease (PD) is the second most common neurodegenerative disorder that affects approximately 10 million people worldwide. The risk of developing PD and similar neurodegenerative disorders increases with age and an estimated 4% people are diagnosed with the disease before reaching the age of 50. Oxidative stress, cytotoxicity, and mitochondrial dysfunction are common features exhibited in the development of PD. The 6‐hyroxydopamine (6‐OHDA) model of PD is one of the most well characterized and studied models of the disease. 6‐OHDA, a neurotoxin, can induce most characteristic features of the disease, including mitochondrial dysfunction in‐vivo and in‐vitro. SH‐SY5Y is a neuroblastoma cell line of human origin that has been used for dose response studies on PD in the past. Based on previous data, we have used SH‐SY5Y cells as an in‐vitro model of PD to analyse the phytomedicinal potential of perillyl alcohol (PA), a monoterpenoid obtained from essential oils of various plants such as sage, peppermint and lavender. We have found that pretreatment with PA (10 μM and 20 μM) mitigated 6‐OHDA (150 μM) induced cytotoxicity in a dose‐dependent manner. We observed marked restoration of cell viability and mitochondrial membrane potential (MMP) as well as reduced reactive oxygen species generation, Cytochrome c immunofluorescence and DNA fragmentation after treatment with PA. On the basis of on our data, we have come to the conclusion that PA demonstrates sufficient neuroprotective activity to provide new avenues in therapy of PD and its apparent target being restoration of MMP can lead to better understanding of the disease.